649. Evaluation of the NG-Test CARBA 5® in Enterobacteriaceae and P. aeruginosa from Clinical Isolates. (4th December 2021) - Mendez-Sotelo, Brauio J; Rodriguez-Zulueta, Patricia; López-Jácome, Luis Esaú; Hernández-Durán, Melissa; Colín-Castro, Claudia Adriana; Martínez-Zavaleta, Guadalupe; Rivera-Buendía, Frida; Velásquez-Acosta, Consuelo; Morfin-Otero, Rayo; Franco-Cendejas, Rafael
Abstract: Background: Identification of carbapenemase-producing organisms like Enterobacteriaceae and P. aeruginosa is important for treatment decisions and infection control. Identification methods require time and technical training. Lateral flow immunoassay NG-Test CARBA 5® exempt these needs. In Mexico there is no evaluation of it on clinical isolates. It is important to define their diagnostic accuracy. Methods: We collected 103 clinical strains of Enterobacteriaceae and P. aeruginosa resistant to carbapenems, from 2019 to 2020 from: National Institute of Rehabilitation (INR), National Institute of Cancerology, General Hospital Dr. Manuel Gea González and Hospital Civil de Guadalajara Fray Antonio Mayor. Analyzed in INR's microbiology laboratory, resistance was corroborated with broth Microdilution Method (CLSI 2020). The carbapenemases was demonstrated by phenotypic methods (CLSI 2021). A homemade PCR was done and sequencing for encoding genes: NDM, KPC, GES, VIM, IMP and OXA-48-like. We analyzed concordance of the NG-Test CARBA 5® versus PCR with kappa coefficient. Results: Seven discarded, 96 strains entered the analysis: Enterobacteriaceae (73%), P. aeruginosa (27%) (Table1). The carbapenemase-producing organisms were: 1) 56 Enterobacteriaceae, 30% Class B; 2) 23 P. aeruginosa, 90% Class B. NG-Test CARBA 5® for Enterobacteriaceae demonstrated greater sensitivity, specificity, and NPV (table 2). Kappa coefficient of concordance was 0.92 for Enterobacteriaceae and 0.59 for P. aeruginosa (table 2), and discrepancies in table 3. Sequencing of carbapenemase-producing organisim can be find in table 4. Title 1. Clinical isolates by hospital N: No carbapenem-producing, Gea: General Hospital Dr. Manuel Gea González, Civil GDL: Hospital Civil de Guadalajara, INCAN: National Institute of Cancerology, INR: National Institute of Rehabilitation. Table 3. Discrepancies Enzyme gene secuencing Conclusion: The most frequent enzyme were Ambler Class B, consistent with national reports. Sensitivity and specificity was like reported in other series. In P. aeruginosa, errors have already been reported in IMP-type enzymes, ours mainly with IMP-75. To our knowledge there are no reports of the following enzyme variants identified by NG-Test CARBA 5®: KPC-82, VIM-67, IMP-62, and IMP-75. NG-Test CARBA 5® showed high concordance with PCR for Enterobacteriaceae, it has the advantage of being a quick and easy-to-use detection tool. In P. aeruginosa despite the results without solid evidence, we recommend complementing the test with other phenotypic identification tests. Table 2. Kappa Concordance Coefficient of NG-Test CARBA 5® and PCR Se: sensitivity, Sp: specificity, PPV: positive predictive value, NPV: negative predictive value Disclosures: All Authors : No reported disclosures